Application of Slow Stroke Back Massage on Blood Pressure Changes in Non-Hemoragic Stroke Patients - Sejati, Ilham Kukuh; Kristinawati, Beti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of slow-stroke back massage in reducing high blood pressure in non-hemorrhagic stroke patients. It uses a descriptive research method in the form of a case study. The study showed that during three slow-stroke back massage interventions, a significant decrease in blood pressure was obtained. In conclusion, slow-stroke back massage is effective in reducing high blood pressure in non-hemorrhagic stroke patients. Keywords: Hypertension, Slow Stroke Back Massage, Non-Hemorrhagic Stroke